An energy-efficiency assessment of Content Centric Networking (CCN) - Butt, M. R.; Delgado, O.; Coates, M. (2012 25th IEEE Canadian Conference on Electrical and Computer Engineering (CCECE), 2012)
Content-Centric Networking (CCN) is a recently proposed networking architecture that can potentially lead to reduced bandwidth usage and better scalability and security as compared to the current IP-based architecture. In this paper, we conduct an energy consumption analysis of content-centric networking and IP-based networking for a video streaming scenario. We consider two types of energy consumption: the energy required to manufacture the network devices and the energy required for operation. We perform simulations of content-centric networking over a general-tree topology to assess the traffic rate reductions achieved by CCN's insertion of caches at routers. Although CCN network devices have a higher intrinsic energy consumption compared to the IP-based devices because of the presence of additional memory, by exploiting their caching capabilities it is possible to reduce the overall energy consumption of the network. We consider both the incorporation of an online rate adaptation mechanism as well as a static network provisioning approach and observe that these approaches can lead to an energy consumption reduction of 10-20 percent.